2017
DOI: 10.17235/reed.2017.4809/2016
|View full text |Cite
|
Sign up to set email alerts
|

A real life study of Helicobacter pylori eradication with bismuth quadruple therapy in naïve and previously treated patients

Abstract: A ten day treatment with BMTO is an effective and safe strategy to combat confirmed H. pylori infection in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
6
13
0
2
Order By: Relevance
“…Our study has several strengths. First, the results are obtained from the largest experience in clinical practice, confirming that the use of this new quadruple therapy is very effective, reaching an eradication rate >90%, in line with other recent real life experiences [17-19]. However, our study differs significantly from those experiences.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our study has several strengths. First, the results are obtained from the largest experience in clinical practice, confirming that the use of this new quadruple therapy is very effective, reaching an eradication rate >90%, in line with other recent real life experiences [17-19]. However, our study differs significantly from those experiences.…”
Section: Discussionsupporting
confidence: 89%
“…We found that TEAEs occurred in about 16% of treated people, and that in only a minority of cases they caused discontinuation of treatment. This TEAE rate was significantly lower than the others reported by the literature, considering both pivotal studies [13, 14] as well as real life ones [16, 19], except for the study of Di Ciaula et al [18]. In our experience, this anti- H. pylori regimen shows a TEAE rate similar to that of standard triple therapy [3].…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations